Evaluation of frequency of paediatric oral liquid medication dosing errors by caregivers: amoxicillin and josamycin. Issue 4 (4th January 2016) - Berthe-Aucejo, A; Girard, D; Lorrot, M; Bellettre, X; Faye, A; Mercier, J C; Brion, F; Bourdon, O; Prot-Labarthe, S
Abstract : Objective: To study reconstitution and preparation dosing errors of liquid oral medications given by caregivers to children. Methods: A prospective observational study was carried out in the departments of general paediatrics and emergency paediatrics at the Robert-Debré Children's University Hospital. An interview with caregivers involved (1) practical reconstitution and preparation of an oral liquid medication from a prescription drawn at random (amoxicillin (Clamoxyl, dosing spoon) or josamycin (Josacine, dose-weight pipette)) and (2) a questionnaire about their use. Results: One hundred caregivers were included. Clamoxyl and Josacine were incorrectly reconstituted in 46% (23/50) and 56% (28/50) of cases, respectively, with a risk of underdosing of Clamoxyl (16/23) and overdosing of Josacine (23/28). Dose preparation with the dosing spoon was incorrect in 56% of cases, and in 10% of cases with the dose-weight pipette. Female sex, native French speaker, and age were significantly associated with correct reconstitution. Male sex and medication were significantly associated with correct preparation. Conclusions: This study highlights the high incidence of errors made by caregivers in reconstituting and preparing doses of these liquid oral medicines, which are associated with considerable risks of over- and underdosing. Factors associated with these errors have been identified which could help health professionals to optimise their strategy for educating families about the use of liquid oral medications and the need to check that they understand these instructions.